Natural radiation events in CCD imagers at ground level. (September 2016) - Saad Saoud, T.; Moindjie, S.; Munteanu, D.; Autran, J.L.
Abstract: In charged coupled devices (CCDs), radiation-induced events generate electron hole pairs in silicon that cause artifacts and contribute to degrade image quality. In this work, the impact of natural radiation at ground level has been characterized at sea level, in altitude and underground for a commercial full-frame CCD device. Results have been carefully analyzed in terms of event shape, size and hourly rates. The respective contributions of atmospheric radiation and telluric contamination from ultra-traces of alpha-particle emitters have been successfully separated and quantified. Experimental results have been compared with simulation results obtained from a dedicated radiation transport and interaction code. Highlights: Image artifacts induced by natural radiation in CCD images are investigated. Radiation-induced events are analyzed in terms of pixel size and hourly rates. Numerical simulations give the contributions of the different particles to the event rates.